PENYEIMBANGAN BEBAN TRANSFORMATOR DISTRIBUSI PCC-007 UNTUK MENGURANGI RUGI-RUGI JARINGAN PADA TEGANGAN MENENGAH 20KV - Muhammad, Fadel; Siagian, Parlin; Fahreza, Muhammad (Power Elektronik : Jurnal Orang Elektro, 2024)
The distribution system of electrical power networks serves as a means to distribute electrical energy to both industrial and household consumers. With the increasing population growth, the number of electrical energy users or consumers also increases, potentially impacting the loading on each distribution transformer. If the loading on each transformer increases, it can lead to overload, load imbalance, power losses, and damage to the transformer. Therefore, to ensure the proper operation of distribution transformers, PLN (a state-owned electricity company in Indonesia) has set a standard for the loading on distribution transformers, which should not exceed 80%. This research aims to measure the loading on distribution transformers and analyze the occurrence of power losses caused by load imbalance. Measurements are conducted using a clamp meter and earth tester to obtain current and voltage values as well as the resistance value of grounding. Subsequently, calculations are performed for transformer loading, load imbalance, and power losses on the feeder.